The Fungus Aspergillus aculeatus Enhances Salt-Stress Tolerance, Metabolite Accumulation, and Improves Forage Quality in Perennial Ryegrass - Li, Xiaoning; Han, Shijuan; Wang, Guangyang; Liu, Xiaoying; Amombo, Erick; Xie, Yan; Fu, Jinmin (Frontiers in Microbiology, 2017)
Perennial ryegrass (Lolium perenne) is an important forage grass with high yield and superior quality in temperate regions which is widely used in parks, sport field and other places. However, perennial ryegrass is moderately tolerant to salinity stress compared to other commercial cultivars and salt stress reduces their growth and productivity. Aspergillus aculeatus has been documented to participate in alleviating damage induced by salinity. Therefore, the objective of this study was to investigate the mechanisms underlying A. aculeatus-mediated salt tolerance and forage quality of perennial ryegrass exposed to 0, 200 and 400 mM NaCl concentrations. Physiological markers and forage quality of perennial ryegrass to salt stress were evaluated based on the growth rate, photosynthesis, antioxidant enzymes activity, lipid peroxidation, ionic homeostasis, the nutritional value of forage and metabolites. Plants inoculated with A. aculeatus exhibited higher relative growth rate (RGR), turf and forage quality under salt stress than un-inoculated plants. Moreover, in inoculated plants, the fungus remarkably improved plant photosynthetic efficiency, reduced the antioxidant enzymes activity (POD and CAT) and attenuated lipid peroxidation (decreased H2O2 and MDA accumulation) induced by salinity, compared to un-inoculated plants. Furthermore, the fungus also acts as an important role in maintaining the lower Na/K ratio and metabolites and lower the amino acids (Alanine, Proline, GABA , and Asparagine) and soluble sugars (Glucose and Fructose) for inoculated plants than un-inoculated ones. Our results suggest that A. aculeatus may be involved in modulating perennial ryegrass tolerance to salinity in various ways.